A social science research agenda to accelerate public engagement in climate change adaptation - Harcourt, Rachel; Dessai, Suraje; Bruine de Bruin, Wandi; Taylor, Andrea (Frontiers in Psychology, 2023)
Recent studies find that people in high-income countries now think of climate change impacts, such as flooding or periods of high temperature, as being of immediate relevance and concern. Individuals and households can take adaptation actions to help limit the likelihood and severity of harm caused when climate impacts occur, for example, they could make adjustments to their homes such as installing flood gates or sun shades, or they could adapt their behaviour such as staying indoors during the hottest part of the day. However, so far adaptation is not yet happening at the speed or scale needed to adequately prepare for the climate impacts already being experienced or those projected for the coming decades. Here, we propose an agenda for future adaptation social science research that would seek to further our understanding of how best to increase adaptation engagement and action.